Survival Boogie Woogie. Neo-Japonisme, Architectural Photography & Abstraction - Cluzel, Jean-Sébastien, (Asian Studies E-Books Online, Collection 2024., 2024)
What links are there between Piet Mondrian's unfinished work Victory Boogie Woogie (1942-4) and post-war Japanese and Japanese-style architectural photography? As far back as the mid-1950s, critics and photographers were inclined to link Mondria